Conductive Copper Niobate: Superior Li+‐Storage Capability and Novel Li+‐Transport Mechanism - Yang, Liting; Zhu, Xiangzhen; Li, Xiaohui; Zhao, Xuebing; Pei, Ke; You, Wenbin; Li, Xiao; Chen, Yongjun; Lin, Chunfu; Che, Renchao (Advanced energy materials, 2019)
Niobates with shear ReO3 crystal structures are remarkably promising anode materials for Li+ batteries due to their large capacities, inherent safety, and high cycling stability. However, they generally suffer from limited rate capabilities rooted in their insufficient electronic and Li+ conductivities. Here, micrometer‐sized copper niobate (Cu2Nb34O87) bulk as a new anode material having a high electronic conductivity of 2.1 × 10−5 S cm−1 and an impressive average Li+ diffusion coefficient of ≈3.5 × 10−13 cm2 s−1 is exploited, which synergistically leads to an excellent rate capability (184 mAh g−1 at 10 C) while remaining a large reversible capacity and superior cycling stability. Moreover, the fast Li+ transport pathways of grain boundary (micrometer scale) → lattice deformation area (nanometer scale) → (010) crystallographic plane (angstrom scale) are demonstrated in Cu2Nb34O87. Therefore, these results could pave the way for practical application of Cu2Nb34O87 in high‐performance Li+ batteries. Microsized Copper Niobate having a high electronic conductivity and an impressive average Li+ diffusion coefficient is fabricated via a conventional solid‐state reaction, which exhibits superior electrochemical performance as an anode material. Research on the Li+ transport reveals the fast Li+ transport pathways of the grain boundary (micrometer scale) → lattice deformation area (nanometer scale) → (010) crystallographic plane (angstrom scale).